2023
DOI: 10.1097/gox.0000000000005305
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of ChatGPT-4 in Plastic and Reconstructive Surgery: A Narrative Review

Fahad K. Aljindan,
Mohammed H. Shawosh,
Lamees Altamimi
et al.

Abstract: Background: ChatGPT-4 (Chat Generative Pre-Trained Transformer) has demonstrated remarkable capabilities in natural language processing and understanding, making it a promising tool for various medical domains. This article presents a comprehensive overview of the potential applications of ChatGPT-4, a cutting-edge language model developed by OpenAI, in the field of plastic and reconstructive surgery. Methods: After conducting a thorough literature revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Apart from helping doctors in clinical diagnosis and treatment, ChatGPT also exhibits remarkable proficiency in clinical paperwork. Researchers have found that ChatGPT could extract pertinent information from medical records and generate a coherent narrative, which could help doctors complete patient notes, operation records and related medical paperwork more efficiently 24 , 27 , 28 .…”
Section: Chatgpt In Medicine: Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from helping doctors in clinical diagnosis and treatment, ChatGPT also exhibits remarkable proficiency in clinical paperwork. Researchers have found that ChatGPT could extract pertinent information from medical records and generate a coherent narrative, which could help doctors complete patient notes, operation records and related medical paperwork more efficiently 24 , 27 , 28 .…”
Section: Chatgpt In Medicine: Prospectsmentioning
confidence: 99%
“…Moreover, ChatGPT can generate detailed case scenarios and produce high-quality exam questions to evaluate the actual level of students. For novice surgeons requiring clinical experience, ChatGPT can simulate surgery procedures, delineate the surgical steps, and elucidate the rationale behind each action, which can help them become familiar with these procedures before the actual operation 27 . Irrespective of regional or institutional variations, clinicians can access uniform and high-quality visual resources for learning and training 25 .…”
Section: Chatgpt In Medicine: Prospectsmentioning
confidence: 99%
“…These results imply that ChatGPT-4 can be a useful tool for helping radiologists produce thorough and precise X-ray reports, which will enhance the workflow in radiology as a whole. Additionally, prior research has demonstrated the potential uses of ChatGPT-4 in musculoskeletal imaging, which highlights the technology's adaptability and usefulness in a range of therapeutic contexts [15]. Healthcare professionals can gain from increased diagnostic process accuracy, consistency, and speed by utilizing ChatGPT-4's capabilities when composing X-ray reports for musculoskeletal disorders.…”
Section: Writing the X-ray Reportsmentioning
confidence: 99%
“…Nonetheless, questions remain about how well AI models will function in complicated domains like medicine, where sophisticated and nuanced reasoning is critical [12]. In order to ensure the appropriate and efficient use of these potent instruments, it is imperative to address potential limitations and ethical issues as the medical community continues to investigate the applications of AI in musculoskeletal imaging [15]. The importance of cutting-edge technology in the field of musculoskeletal imaging, such as Sono elastography for tendon assessment and 3 Tesla field strength for MRI, has been emphasized [23][24][25].…”
Section: Future Considerations Of Artificial Intelligence In Musculos...mentioning
confidence: 99%
“…LLMs like ChatGPT show great promise in terms of being useful in healthcare, especially in surgery. The surgical applications of LLMs include assisting in personalized surgical consultations [6][7][8], facilitating the informed consent process [6,9], enhancing patient communication and instructions [8][9][10], and contributing to the education of surgical trainees [8,9,11,12]. Nevertheless, the emergence of these models has stirred considerable debate within the academic and medical community, primarily due to concerns over inherent biases [13][14][15][16], patient data privacy [17,18], and the propagation of misinformation [19].…”
Section: Introductionmentioning
confidence: 99%